Physiological characteristics associated with increased resistance to decompression sickness in male and female rats. - Lautridou, Jacky; Dugrenot, Emmanuel; Amérand, Aline; Guernec, Anthony; Pichavant-Rafini, Karine; Goanvec, Christelle; Inizan, Manon; Albacete, Gaelle; Belhomme, Marc; Galinat, Hubert; Lafère, Pierre; Balestra, Costantino; et al. (2020)
Decompression sickness (DCS) is a complex and poorly understood systemic disease with wide inter-individual resistance variability. We selectively bred rats with a 3-fold greater resistance to DCS than standard ones. To investigate possible physiological mechanisms underlying the resistance to DCS, including sex-related differences in these mechanisms, 15 males and 15 females resistant to DCS were compared with aged-matched standard Wistar males (n=15) and females (n=15). None of these individuals had been previously exposed to hyperbaric treatment. Comparison of the allelic frequencies of SNPs showed a difference of one SNP located on the X chromosome. Compared with non-resistant rats, the neutrophil-to-lymphocyte ratio and the plasmatic activity of coagulation Factor X were significantly higher in DCS-resistant individuals regardless of their sex. The maximal relaxation elicited by sodium nitroprusside was lower in DCS-resistant individuals regardless of their sex. Males but not females resistant to DCS exhibited higher neutrophil and lymphocyte counts, higher prothrombin time whereas lower mitochondrial basal O2 consumption and citrate synthase activity. Principal Components Analysis showed that two principal components discriminate the DCS-resistant males but not females from the non-resistant ones. These components were loaded with aPTT, MLR, PT, FX, Fib, for PC1, and ARBC and ANC for PC2. In conclusion, the mechanisms which drive the resistance to DCS appear different between males and females; lower coagulation tendency and enhanced inflammatory response to decompression stress might be key for resistance in males. The involvement of these physiological adaptations in resistance to DCS must now be confirmed.